Rocky Mountain Bird Observatory: conserving birds and their habitats - Quattrini, Laura, author (Colorado State University. Libraries, 2009)
The mission of the Rocky Mountain Bird Observatory (RMBO) is to conserve birds and their habitats of the Rocky Mountains, Great Plains, and Intermountain West. We accomplish our mission through science, education and stewardship. RMBO's science provides the knowledge to drive conservation action. Our Education Program instills a conservation ethic and uses birds as a tool to engage youth and adults in the outdoors. Our stewardship works with agricultural producers to increase awareness of wildlife and implements on-the-ground conservation.
Rocky Mountain Bird Observatory: raising awareness and opening doors for conserving birds and their habitats
Presented at the Bridging the gap: collaborative conservation from the ground up conference, September 8-11, 2009, Colorado State University, Fort Collins, Colorado, sponsored by the Center for Collaborative Conservation, https://collaborativeconservation.org/. This conference brought together people with experience working collaboratively to achieve both conservation and livelihood goals in tribal nations, rangelands, forests, watersheds, agricultural lands, and urban areas. The presenter is affiliated with Rocky Mountain Bird Observatory.
Keywords: bird conservation; Prairie Partners; RMBO; Rocky Mountain Bird Observatory; Private Lands Wildlife Biologist Program; PLWB